Enhancing Students’ Reading Comprehension By Using Authentic Material At Grade VIII B Of SMPN 57 Surabaya Academic Year 2022/2023 - Umul Khasanah; Nining Fitriani; Akiko Rahmawati; Dian Eka Priyantoro; Gamar Al Haddar; Everhard Markiano Solissa (Journal on Education, 2023)
Reading is what happens when people look at a text and assign meaning to the written symbols in that text. It functions as a major tool for finding and understanding information in terms of what is already known. Reading also has the value of helping the students learn to express their own thoughts and make them familiar with the language patterns and ways of using language efficiently. Students at grade VIII B of SMPN 57 Surabaya academic year 2018/2019 get many problems dealing with reading. The purposes of this research were to find out to find whether authentic material can improve student’s reading comprehension and to know the factors that influence students’ reading comprehension by using authentic material. This research was classroom action research. The subject used by the researcher was second grade students (grade VIII B) of SMPN 57 Surabaya. Based on the data analyzed, it shown that authentic teaching materials could improve students’ reading comprehension. It could be proven by looking at the change on students’ behaviors. Before using authentic teaching materials as the technique, the classroom situation was boring and lifeless, but after using the technique, there was a new atmosphere which motivated the students. The students became more enthusiastic in reading than before. Besides, their achievement also improved. It could be seen that the mean score in pre-test 55.5 increased to 77.6. Thus, the researcher concludesd that teaching students reading comprehension using authentic teaching materials could improve the students’ reading comprehension, increase their vocabulary, encourage them to be active.